2017
DOI: 10.2147/ott.s125497
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of serous cystadenoma from mucinous cystadenoma in the pancreas with contrast-enhanced ultrasonography: a prospective study in 61 patients

Abstract: ObjectivesThe preoperative diagnosis between serous cystadenomas (SCAs) and mucinous cystadenomas (MCAs) in pancreas is significant due to their completely different biological behaviors. The purpose of our study was to examine and compare detailed contrast-enhanced ultrasonography (CEUS) images of SCAs and MCAs and to determine whether there are significant findings that can contribute to the discrimination between these two diseases.MethodsFrom April 2015 to June 2016, 61 patients (35 patients with SCAs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
6
5
0
Order By: Relevance
“…The BD-IPMNs are composed of cysts that communicate with the main pancreatic duct [12]. Both IPMN and pseudocysts are predominant in men and are prone to pancreatitis [13, 14]. Our study revealed that SCNs and MCNs occurred more frequently in women, which was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The BD-IPMNs are composed of cysts that communicate with the main pancreatic duct [12]. Both IPMN and pseudocysts are predominant in men and are prone to pancreatitis [13, 14]. Our study revealed that SCNs and MCNs occurred more frequently in women, which was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…When any two imaging features were combined, we obtained the highest Az value (0.824) in diagnosing SCNs, as well as the appropriate sensitivity (84.2%), specificity (80.6%), PPV (84.2%), NPV(80.6%) which was almost consistent with study by Sun Y [14]. The four specific imaging features used in the study by Sun Y [14] for the diagnosis of SCNs were head/neck location, lobulated shape, thin wall (0–2 mm) and honeycomb pattern, which were slightly different from the imaging features used in our study. We believed that the honeycomb pattern was more specific for the diagnosis of SCNs than the number of septa > 2 but excluded a large portion of atypical SCNs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[19] Sun et al showed honeycomb pattern is seen in serous cystadenoma and side branch IPMT whereas none of the mucinous cystadenoma showed honeycomb pattern. [21] Honeycomb appearance is seen in serous cystadenomas and side branch IPMT but rarely has been reported in mucinous cystadenoma. [22] Mucinous cystadenomas have thick (>3 mm) wall and serous cystadenomas have thin wall (<3 mm).…”
Section: Discussionmentioning
confidence: 99%
“…19 There are several published reports of using CEUS in PCLs, which proved that CEUS can play a vital role in improving the diagnostic rate of pancreatic cystic lesions. 12,13,[20][21][22] However, no study has compared the diagnostic performance of CEUS with CT and MRI in pancreatic neoplasms. In this study, we prospectively compared the diagnostic capability of CT, MRI, and CEUS of 90 patients with PCNs who were finally confirmed surgicopathologically and analyzed the mainly detailed characterization of these lesions.…”
Section: Introductionmentioning
confidence: 99%